Analysing interactions in a teacher network forum: a sociometric approach - Lisbôa, Eliana Santana (2013)
This article presents the sociometric analysis of the interactions in a forum of a social network created for the professional development of Portuguese-speaking teachers. The main goal of the forum, which was titled Stricto Sensu, was to discuss the educational value of programmes that joined the distance learning model in Brazil. The empirical study focused on the sociometrie analysis of the social interactions that take place in asynchronous online environments. This approach, according to literature, allows for new means to observe, analyse, and interpret the reality of a new social paradigm. This type of analysis tries to understand the relationship established between the different actors, seeking to verify if the roles they play in both the access to information and the construction of shared knowledge. The data collected allow the researchers to deduce that the indicators used in the analysis are important for understanding and intervening in the dynamics and functioning of the network to propose improvements in its structure and organisation. In the specific case of the aforementioned discussion forum, the results of the sociometrie analysis of the perceived interactions were not surprising, considering that the nature of the topic did not demand deep reflection to contribute to the debate.